Detection of Mycobacterium tuberculosis by Microscopic Technique of Sputum AFB and ICT (Cocktail Antigen) TB - Retno Martini Widhyasih; Annisa Husnun Hanifah; Chairlan Chairlan; Dewi Inderiati (Medical Laboratory Technology Journal, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. The diagnosis of pulmonary TB in general still relies on microscopic examination with a sputum smear for Acid Fast Basil (AFB). Microscopic examination to detect M. tuberculosis has high specificity, but the sensitivity is 35-70%. The sputum culture method is the gold standard for the diagnosis of pulmonary TB but requires a long time, which is 6-8 weeks. In recent years ICT (Immuno Chromatography Test) has been introduced to identify potential and useful TB antigens to help diagnose pulmonary TB. Antigens detected were ESAT-6, CFP-10, CFP-21, and MPT-64. This study aims to compare the results of the examination of specimens of suspect TB sputum with the ICT method and AFB. This study based on observational with analytic design cross-sectional on 56 samples of Stored Biological Material suspects TB that were examined by the AFB method and the ICT method (Cocktail Antigen). Statistical test results Fisher Exact (α = 0.05) showed no difference between microscopic examination of smear sputum and ICT (Cocktail Antigen) TB (p = 1,000). Nevertheless, the use of ICT reagents for the diagnosis of pulmonary TB still needs to be further investigated, especially to find out the exact causes of false positive and false negative reactions.